HUSBAND'S SUPPORT RELATIONSHIP WITH EXCLUSIVE BREASTFEEDING OF INFORMAL WORKING WOMEN IN THE WORKING AREA OF DELI TUA HEALTH CENTER IN 2022 - Peny Ariani; Putri Ayu Yessy Ariescha; Rani Mariana (JURNAL KESMAS DAN GIZI (JKG), 2022)
Exclusive breastfeeding is giving only breast milk without giving other foods and drinks to babies from birth to 6 months of age, except for drugs and vitamins and still given to babies until the baby is 2 years old (WHO, 2011). Exclusive breastfeeding coverage in Indonesia in the last five years has decreased from 38% in 2013 to 37.5% in 2018. This figure is still far from the target that must be achieved, which is 80%. So it is necessary to study the factors that cause the low coverage of exclusive breastfeeding. Husband's support is considered as a factor that plays a role in exclusive breastfeeding. Because in order to ensure the success of exclusive breastfeeding for women working informally, it is necessary to have family support, especially husband's support. For this reason, it is necessary to conduct research on the relationship between husband's support and exclusive breastfeeding for women working informally. This type of research is a non-experimental research with a cross sectional design. Analysis of the data using the chi square test with a sample of 57 women informal workers who have babies aged 6-12 months. This study aims to examine the relationship between husband's support and exclusive breastfeeding for women working informally in the Deli Tua Health Center Work Area, East Deli TuaDistrict, Deli Serdang Regency. The results showed that there was a relationship between husband's support and exclusive breastfeeding (?=0.003). From the results of the study, it is suggested to health workers, especially midwives, to increase the intensity of providing information through counseling, distributing media such as leaflets not only to mothers but to husbands and families as well as motivating mothers who are giving birth or checking their pregnancies to the puskesmas to give exclusive breastfeeding to their babies.